Electrical energy efficiency of dye sensitized solar cells by polymer electrolyte - Santhaveesuk, Surasak; Kahattha, Chokchai; Ponhan, Witawat (Creative Science, 2024)
This research aims to prepare by mixtures method with dope carbon black as a working electrode and the apply it to the dye sensitized solar cells (DSSCs). The thin film of titanium dioxide nanocrystalline semi - conductor with dope carbon black, the cells were coated on to transparent conducting oxide glass sheet by means of the doctor blade technique as a working electrode. But the polymer electrolyte were prepare by adding potassium iodide and iodine salts with a ratio of KI:I2 was 10:1, into a polymer electrolyte composed of poly-ethylene glycol, ethylene carbonate and poly(styrene–co–acrylonitrile). The polymer electrolyte mixtures became homogeneous and stirring at a temperature of 80 °C. Found that efficiency for the DSSCs by polymer electrolyte based on yielded an overall light to electrical energy conversion efficiency ( ) of the DSSCs was 5.5095%, An open-circuit voltage of 0.58 V, voltage at the point of maximum power output of 0.42 V, short-circuit current density of 11.11 mA.cm–2, current density at the point of maximum power output of 10.50 mA.cm–2 fill factor of 0.684 under an irradiation of 80 mW.cm–2. And the long-term stability test of the DSSCs with a polymer electrolyte is evidently superior to the DSSCs with liquid electrolyte based on the observation period lasting for 90 days. GRAPHICAL ABSTRACT HIGHLIGHTS prepare by mixtures method with dope carbon black as a working electrode The efficiency for the DSSCs by polymer electrolyte based on yielded an overall light to electrical energy conversion